Estimating the Number of Civilian Casualties in Modern Armed Conflicts–A Systematic Review - Khorram-Manesh, Amir; Burkle, Frederick M.; Goniewicz, Krzysztof; Robinson, Yohan (Frontiers in Public Health, 2021)
Objective: To examine the possibility of estimating the number of civilian casualties in modern armed conflicts. Methods: A systematic review was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, using PubMed, Scopus, and Web of Science search engines. The outcome was analyzed using a qualitative inductive thematic analysis. The scientific evidence of selected article was assessed, using the Health Evidence Quality Assessment Tool. Findings: The review of 66 included articles in this study indicates that with an increasing number of public health emergencies and the lack of vital elements of life such as water and food, emerging armed conflicts seem to be inevitable. In contrast to military-led cross-border traditional wars, modern armed conflicts affect internally on local communities and take civilian lives. Consequently, the measures and tools used in traditional military-led cross-border wars to adequately tally wounded and dead for many decades under the mandates of the International Humanitarian Law, is insufficient for modern warfare. While casualty counting during modern conflicts is deficient due to organizational, political or strategic reasons, the international organizations responsible for collecting such data (the International Federation of Red Cross and Red Crescent and International Institute of Humanitarian Law) face difficulties to access the conflict scene, resulting in under-reported, unreliable or no-reported data. Conclusion: There are challenges in estimating and counting the number of civilian casualties in modern warfare. Although the global need for such data is evident, the risks and barriers to obtaining such data should be recognized, and the need for new international involvement in future armed conflicts should be emphasized.